Attributable Mortality of Healthcare-Associated Infections Due to Multidrug-Resistant Gram-Negative Bacteria and Methicillin-Resistant Staphylococcus Aureus. (1st June 2017) - Nelson, Richard E.; Slayton, Rachel B.; Stevens, Vanessa W.; Jones, Makoto M.; Khader, Karim; Rubin, Michael A.; Jernigan, John A.; Samore, Matthew H.
Abstract : OBJECTIVE: The purpose of this study was to quantify the effect of multidrug-resistant (MDR) gram-negative bacteria and methicillin-resistant Staphylococcus aureus (MRSA) healthcare-associated infections (HAIs) on mortality following infection, regardless of patient location. METHODS: We conducted a retrospective cohort study of patients with an inpatient admission in the US Department of Veterans Affairs (VA) system between October 1, 2007, and November 30, 2010. We constructed multivariate log-binomial regressions to assess the impact of a positive culture on mortality in the 30- and 90-day periods following the first positive culture, using a propensity-score–matched subsample. RESULTS: Patients identified with positive cultures due to MDR Acinetobacter (n=218), MDR Pseudomonas aeruginosa (n=1, 026), and MDR Enterobacteriaceae (n=3, 498) were propensity-score matched to 14, 591 patients without positive cultures due to these organisms. In addition, 3, 471 patients with positive cultures due to MRSA were propensity-score matched to 12, 499 patients without positive MRSA cultures. Multidrug-resistant gram-negative bacteria were associated with a significantly elevated risk of mortality both for invasive (RR, 2.32; 95% CI, 1.85–2.92) and noninvasive cultures (RR, 1.33; 95% CI, 1.22–1.44) during the 30-day period. Similarly, patients with MRSA HAIs (RR, 2.77; 95% CI, 2.39–3.21) and colonizations (RR, 1.32; 95% CI, 1.22–1.50) had an increased risk of death at 30 days. CONCLUSIONS: We found that HAIs due to gram-negative bacteria and MRSA conferred significantly elevated 30- and 90-day risks of mortality. This finding held true both for invasive cultures, which are likely to be true infections, and noninvasive infections, which are possibly colonizations. Infect Control Hosp Epidemiol 2017;38:848–856